Isolasi dan Karakterisasi Asam Humat dari Tanah Dasar Bendungan Batujai Lombok Tengah NTB - Nurul Ismillayli; Dhony Hermanto (Al-Kimia, 2019)
This study deals with the isolation and characterization of humic acids from Batujai Dam subgrade, Central Lombok. Humic acid isolated by using recommended method of the International Humic Substances Society and purified by 0.1M HCl/0.3 M HF solution. Humic acid isolated then were determined ash content, total acidity, carboxilic and phenolic group content and characterized using FTIR spectroscopy.  FTIR analyses of isolated humic acid samples have shown the presence of carboxylic, phenols, alcoholic, amines functional groups, aliphatic hydrocarbon and aromatic ring. The result of ash content determination showed that purification decreased ash content from 5.60% to 1.13%. Total acidity of humic acid was 630 cmol/kg, acidity of –COOH was 226 cmol/kg, and –OH fenolic acidity was 404  cmol/kg.